2001
DOI: 10.1021/jf010128f
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacities and Phenolics Levels of French Wines from Different Varieties and Vintages

Abstract: Phenolics from grapes and wines can play a role against oxidation and development of atherosclerosis. Levels of phenolics, major catechins [(+)-catechin, (-)-epicatechin, procyanidin dimers B1, B2, B3, and B4], phenolic acids (gallic acid and caffeic acid), caftaric acid, malvidin-3-glucoside, peonidin-3-glucoside, and cyanidin-3-glucoside were quantified by HPLC with UV detection for 54 French varietal commercial wines taken from southern France to study the antioxidant capacity and the daily dietary intake o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
182
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(234 citation statements)
references
References 18 publications
48
182
2
2
Order By: Relevance
“…In addition, concentrations of total phenolics determined in apple wines were consistent with those previously studied, reporting 228-801 mg/L (11,12,23,24). Concentrations of total phenolics found in blackcurrant, cherry and blackberry fruit wines were close to those found in red wine (1018-4059 mg/L) (36)(37)(38). On the other (23) reported that the concentrations of phenolics in elderberry, blueberry and blackcurrant wines were comparable to red, and in apple and peach wines to white wine.…”
Section: Total Phenolics and Total Anthocyanins In Fruit Winessupporting
confidence: 88%
“…In addition, concentrations of total phenolics determined in apple wines were consistent with those previously studied, reporting 228-801 mg/L (11,12,23,24). Concentrations of total phenolics found in blackcurrant, cherry and blackberry fruit wines were close to those found in red wine (1018-4059 mg/L) (36)(37)(38). On the other (23) reported that the concentrations of phenolics in elderberry, blueberry and blackcurrant wines were comparable to red, and in apple and peach wines to white wine.…”
Section: Total Phenolics and Total Anthocyanins In Fruit Winessupporting
confidence: 88%
“…Values within a column followed by different letters in superscripts are significantly different by Tukey's test after ANOVA (P < 0.05) ND not detected acid. Previously, LDL oxidation preventing ability of red wine was found to be greater than that of α-tocopherol (Landrault et al 2001). The activity of solids collected on the 10th day of fermentation was the lowest in all varieties (data not shown).…”
Section: Comparison Of Antioxidant Assays Of Different Species Of Phymentioning
confidence: 67%
“…A relationship between TAC and total phenol content of wines has previously been shown (Landrault et al, 2001;De Beer et al, 2003). The trend for TACCAL of the 2002 wines could mainly be explained by a higher contribution by caftaric acid, (+)-catechin, procyanidin B1 and quercetin for region II wines, compared to wines from the other regions.…”
Section: Effect Of Climatic Regionmentioning
confidence: 77%